A Bánság térfejlődésének közigazgatás-történeti csomópontjai 1918-ig - Hajdú, Zoltán (Közép-Európai Közlemények, 2010)
The Banat (Bánság) is a very special area of the Historical Hungary. It was formed in 1718 as a special public administrative unit. The Banat was nearly depopulated and the main task was repopulate the region. Settlers were arriving from different parts of Europe and Habsburg Empire. In 1778, the Banat region was admininistratively joined with Hungary. Three counties were organised on the former territory of Banat. Temesvár (Timisoara) turned to be not just capital of Temes County, but functional capital of the whole region. After 1918, the former territory of Banat were divided between three (Hungary, Yugoslavia, Romania) countries.